Emotional quotient of the Administration and Commercial Management students of a private university - Rojas Samanez, Lita Regina (2019)
This research study’s objective is to determine the predominant dimension in the emotional quotient of the Business Management and Administration students of a private university of Peru. The research was substantive, non-experimental, descriptive- explanatory and cross-sectional. The instrument used to evaluate the variable was the of Emotional Quotient questionnaire (Cooper & Sawaf, 1997), which is composed of 262 questions, and it was applied on a sample of 86 university students. The results show that the values and beliefs dimension (B = 1.814) has a higher coefficient and, thus, contributes more to the emotional quotient of the students analyzed. This dominant part of the results of the dimension presented an odds ratio (Exp(B)) = 6.134, which shows that this is a dimension of risk, which would lead a student to have 6.134 times greater possibility of presenting low levels of emotional quotient with respect to another with high levels of emotional quotient because of the dimension values and beliefs.